Prototyping a scalable smart village (B) - Darwin, Solomon; Chesbrough, Henry William; Rotter, Kimberly B. (London : The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business, 2018)
This case focuses on the development of Smart Villages in the state of Andhra Pradesh (AP), India. The case study allows students to consider how to overcome economic, cultural and political obstacles in order to engage in Open Innovation that inevitably leads to wealth creation and greater happiness. The directors of Smart Villages must find a way to encourage investment and effect a cultural shift while navigating deeply entrenched but ineffective present systems.
Originally Published InDarwin, S., Chesbrough, H., & Rotter, K. (2018). Prototyping a scalable smart village (B). The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Smart cities -- India -- Andhra Pradesh -- Case studies; City planning -- India -- Andhra Pradesh -- Case studies; Housing -- India -- Andhra Pradesh -- Case studies; Infrastructure (Economics) -- India -- Andhra Pradesh -- Case studies